ANALISIS COMMON SIZE DAN RASIO KEUANGAN PADA SUBSEKTOR WHOLESALE (DURABLE & NON-DURABLE GOODS) YANG TERCATAT DI BEI - Nuru Riani; Zulkarnain Zulkarnain (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2020)
The purpose of this research was to calculate and analyse the financial performance of the Wholesale Durable & Non-Durable Goods Subsector that were listed on the Indonesia Stock Exchange for the period 2017 and 2018 by using the financial ratio and common size method. The financial ratio method used liquidity ratios (CR, QR, and cash ratio.), solvency (DAR and DER), activity (total assets turnover and inventory turnover), and profitability (GPM, NPM, and ROE). This reseach used secondary data in the form of statement of financial position and income statements. The method used was descriptive quantitative. The conclusion of the calculation using the financial ratio method was the company has been classified as less good that the results were not suit with the industry standards. For the calculation used common size, indicated that assets and equity decreased, while liabilities increased.